"I want to define myself by what I am instead of what I am not": Examining Gender and Sexuality in Contemporary US Graphic Memoirs - Davies, Caitlin (2021)
This thesis explores the themes of gender and sexuality in contemporary US graphic memoirs. I argue for the exceptionalism of the graphic narrative form for portraying this subject matter through the powerful combination of the visual and the verbal. Using life writing, gender theory, queer theory, and comics theory, my interdisciplinary approach explores the recent outpouring of graphic memoir, and its capability of conveying emotional truth. I identify a gap in research concerning a canon of queer comics, predominantly contributed to by women and non-binary artists that have traditionally been marginalised. Chapter 1 examines the formal elements of Phoebe Gloeckner’s The Diary of a Teenage Girl, contributing to existing discourse surrounding its ambiguous genre. I consider what Gloeckner’s illustrations add to her diary entries from her adolescence by introducing key concepts and vocabulary from comics and life writing forms. Chapter 2 compares Maggie Thrash’s Honor Girl and Tillie Walden’s Spinning in their treatment of emotional truth, and the structures of the homosocial and the closet. I analyse how both writers are outed by an authority figure during their adolescence in the American South, and how they reclaim the agency over sexual identity. Chapter 3 explores how Maia Kobabe’s Gender Queer portrays coming out as non-binary and asexual. I observe how Kobabe challenges gender binaries, pronoun use, and what is considered ‘natural’ by society through eir use of images of the natural world.